Prospective monitoring of health problems among recreational runners preparing for a half marathon. Issue 1 (23rd January 2018) - Hollander, Karsten; Baumann, Antje; Zech, Astrid; Verhagen, Evert
Abstract : Objectives: While the health benefits of running are legitimately advocated, participation in running can also lead to health problems. There is a high range of reported prevalence rates especially of running-related overuse injuries in high-level athletes and during competition. Little consensus exists for acute injuries and illnesses especially in recreational runners. Therefore, the aim of this study was to record the prevalence of health problems in recreational long-distance runners preparing for an event. Methods: Recreational runners aged 18–65 years who were registered 13 weeks prior to a half-marathon running event were invited to take part in this study. Participants were prospectively monitored weekly over 13 weeks by applying a standardised surveillance system for injuries and illnesses (Oslo Sports Trauma Research Center questionnaire). From this, prevalence and severity of acute and overuse injuries, as well as illnesses, were calculated. Results: We received 3213 fully answered questionnaires from 327 participants (40.7% female, 40.9±11.7 years of age, 31.5±21.1 km weekly mileage, 8.3±7.8 years of running experience). At any point in time over the preparation phase, 37.3% of the participants had health problems. Overuse injuries were the major burden (18%). They were followed by illnesses (14.1%) and acute injuries (7.9%). The median weekly severity score was 56.5 (IQR 37.0–58.0). Conclusion: The high prevalence of health problems in our cohort suggests that future efforts are needed to further specify the underlying mechanism and develop adequate prevention strategies for recreational runners.